Characterization of Robusta Coffee Powder with Addition of Palm Sugar and Vanilla Powder to Improve The Quality of Robusta Coffee (Coffea canephora Pierre) - Herliani, Canserlita Puteri; Savitri, Dyah Ayu; Suud, Hasbi Mubarak; Rosyady, Muhammad Ghufron (International Journal on Food, Agriculture and Natural Resources, 2024)
Bondowoso Robusta Coffee is a type of Robusta coffee that has a distinctive taste and high quality. The distinctive taste and high quality are obtained from the results of harvest management and post-harvest processing in accordance with Standard Operating Procedures (SOP). This research will be carried out by testing the characteristics of Robusta ground coffee with a mixture of palm sugar and vanilla flavoring to improve the quality of Robusta ground coffee. This was done by knowing the physicochemical and organoleptic properties of the mixed Robusta ground coffee. The aim of this research is to determine the interaction between roasting level and the composition of palm sugar and vanilla powder on the physiochemical and organoleptic properties of 3 in 1 Robusta Coffee. This research uses an experimental plan arranged factorially with the basic pattern of a Completely Randomized Design (CRD) with 4 replications. This design has two factors, the first factor is the roasting level and the second is the mixture composition. The results of this research show (1) The interaction of Roasting Level and Mixture (palm sugar and vanilla powder) has no significant effect on all observed variables such as water content, Brix content, pH value, and powder bulk density. (2) The effect of the main level of roasting has a very significant effect on the observed variables of rainfall density and an insignificant effect on the variables of air content, Brix content and pH value. (3) The effect of the main mixture has a very significant effect on the observed variables of air content, Brix content and powder bulk density and has no significant effect on the variable pH value.